Korelasi Al-Qur’an Dengan Sains Dan Matematika Sebagai Sumber Kebenaran Dalam Pembuktian Nilai Π (Phi) Dari Peristiwa Tawaf - Hasan, Hasan; Al-idrus, Syayid Qosim M Jafar (International Conference on Islamic Studies, 2020)
The discussion regarding the correlation between the Qur'an, science and mathematics has been widely studied in recent times. As an entity that is very different when looking at the three, it is impossible to compare it. However, there is a different point of view when looking for the related relationships between the three in events in the universe in worship activities or in everyday life. Al-Qur'an which is essentially present as the holy book for Muslims is able to provide the truth for the reality of science and mathematics is present for the approval of scientific certainty. the interpretation of the verses of the Al-Qur'an relating to the events of the universe is also growing. Science and mathematics always form a whole circle in their quest to find true new knowledge. The second movement is in an effort to find the correct regularity patterns from the various regular patterns. In this study, we focus on proving the value of π (phi) from the Tawaf Incident by taking into account the correlation of the Qur'an, science and mathematics. The method used in this study is a qualitative method, while the type of research is literature study.